1993
DOI: 10.1288/00005537-199303000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and paranasal sinus anomalies in children with chronic sinusitis

Abstract: Functional endoscopic sinus surgery (FESS) is being advocated to treat children with chronic sinusitis. The surgeon performing FESS needs an intimate understanding of the anatomy to adequately treat disease and avoid complications. One hundred thirty-six patients who had endoscopic sinus surgery were reviewed. Preoperative direct coronal computed tomography scans were available for review in 114 patients. Several nasal and paranasal sinus anomalies were uncovered during this evaluation. The most common was hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 13 publications
2
52
0
3
Order By: Relevance
“…In a previous study of 114 cases Milczuk et al [12] found the uncinate process to be laterally bent in 11 cases (9.64 %). The exact prevalence of these variations and their relation to sinus disease is not determined.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous study of 114 cases Milczuk et al [12] found the uncinate process to be laterally bent in 11 cases (9.64 %). The exact prevalence of these variations and their relation to sinus disease is not determined.…”
Section: Discussionmentioning
confidence: 90%
“…As a consequence of various anatomic and functional relationships immediately adjacent to the OMC, proliferation of disease into the anterior sinuses is natural [4,12]. Nasal endoscopic examination in conjunction with CT scan has proven to be ideal combination in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Several radiographic studies have shown a significant relationship between Haller cells' size (greater than 3 mm) and maxillary sinusitis. [5][6][7] To date, there have been few studies comparing image quality in cone beam CT (CBCT) scans with that in multislice CT. 8 Cadaver and clinical studies have provided the principle evidence for the application of CBCT imaging to endoscopic sinus surgery, concluding that both spatial and soft-tissue contrast were sufficient to aid surgical navigation in the sinonasal cavity. [9][10][11] Preliminary evidence suggests that CBCT may be suited to specific imaging tasks in the context of bony structural evaluations enabling low-dose assessment of sinonasal anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…One prevailing theory considers that ongoing inflammatory mucosal disease leads to decreased pneumatization similar to poor temporal bone pneumatization in chronic otitis media. 46 The general lack of chronic ear disease in CF patients and normal temporal bone development argues against this hypothesis. 47 However, genotype does appear to influence paranasal sinus development as individuals homozygous for the F508del mutation have shown a significantly increased frequency of underdeveloped frontal (98%), maxillary (70%), and sphenoid (100%) sinuses when compared with other genetic mutations (69,8, and 50%, respectively), suggesting CFTR may be a primary contributor to sinus development.…”
Section: Pathophysiology Of Crsmentioning
confidence: 99%